Analisis Peningkatan Mutu Pelayanan Dalam Usaha Menghimpun Dana Masyarakat (Tabungan) Pada PT Bank Rakyat Indonesia (Persero) Tbk Unit Simalingkar Medan - Matondang, Puteri Aiko Nadia; Astuty, Fuji (Jurnal Ekonomi Bisnis Digital, 2022)
Bank is a financial institution that generally established with the authority to accept deposits, lend money and issue promissory notes. Delivering high quality services is not easy. Service quality focuses on customer satisfaction in meeting the wants and needs to be able to achieve customer expectations. Banks must try to improve services so that banks are able to provide the needs or desires of customers. The research method used is field research with a qualitative approach. The location of this research was carried out at PT Bank Rakyat Indonesia Unit Simalingkar Medan. The procedure for obtaining information uses observation and interview techniques. Based on the results of the study, it can be concluded that the implementation of the quality implementation that has occurred at PT Bank Rakyat Indonesia Unit Simalingkar Medan has been carried out in accordance with applicable standards and procedures and strategies that can be used to increase customer savings are promotional strategies, pick up the ball and maintain relationships good with customers.